JUSTIFICATION OF SYSTEMS OF OPEN CAST DEVELOPMENT OF USEFUL FOSSILS AND THEIR NEW CLASSIFICATION - Rakishev B. (Scientific Journal of Pedagogy and Economics, 2020)
To substantiate the new definition of an opencast development system of minerals, the standard approaches of the systems analysis are used. The patterns of moving of the mine workings in the quarry field are expressed through the analytically found velocities of moving the bench face, moving of the bench slope and the deepening of the quarry bottom. These kinematic characteristics of the moving of mine workings are the basis for the classification of the opencast development systems. A new well-reasoned definition of an opencast development system is given. The properties inherent in it as in any system are disclosed: organization, structure, connections and functions. A new classification of the minerals opencast development systems has been created. The velocities of the bench face moving, the bench slope moving and the quarry bottom deepening were found analytically. These kinematic characteristics of the moving of the development system elements are successfully correlated their parameters with the productivity of the excavating and loading equipment. It is substantiated for the first time that the complex of the interdependent and interconnected with each other the development, stripping and excavating workings, moving at the quarry field by time for rock extraction from the Earth bowels, is a system of the minerals opencast development. For the first time in the mining science, the kinematic characteristics of the moving of mine workings in a quarry field have been theoretically found. The format of the new classification of the minerals opencast development systems is substantiated. The proposed new classification of minerals opencast development systems and the kinematic characteristics of moving of the mine workings in the quarry field make it possible to reasonably choose the development subsystems, their parameters and indicators in relation to the working dimensions of excavating and loading equipment, transport, and opencast mining technology. This solution provides a safe, high-performance, economical mining operation in the quarry.